Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10457-010-9357-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation of baobab (Adansonia digitata L.) fruit traits in Mali

Abstract: We analyzed the phenotypic variation of baobab (Adansonia digitata L.) fruits from Mali to define the domestication potential of this species. 269 trees, selected from 10 provenances distributed along a rainfall gradient, were characterized. Five fruits were sampled from each tree. Total individual fruit weight was partitioned into shell, pulp, and seed weight. Ratios were calculated between pulp ? seed and total weight, and between pulp and seed weight. For all the measured fruit traits, we detected significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Our results compare favourably with several published literature on baobab phenotypic variations: (Barwick 2004;Carr 1958;De Smedt, et al 2011;FAO, 1982;Gebauer et al 2002;Gruenwald and Galiza 2005;Nour et al 1980). Gruenwald and Galiza (2005) reported that the percentage of fruit pulp varies according to the origin.…”
Section: Fruit Variation Between and Within Provenancessupporting
confidence: 92%
See 4 more Smart Citations
“…Our results compare favourably with several published literature on baobab phenotypic variations: (Barwick 2004;Carr 1958;De Smedt, et al 2011;FAO, 1982;Gebauer et al 2002;Gruenwald and Galiza 2005;Nour et al 1980). Gruenwald and Galiza (2005) reported that the percentage of fruit pulp varies according to the origin.…”
Section: Fruit Variation Between and Within Provenancessupporting
confidence: 92%
“…FAO (1982) have also reported baobab fruit size of up to 35 cm length by 8 to 15 cm width. De Smedt et al (2011) have reported mean pulp yield per fruit of 45 ± 1g and seed production of 71 ± 2g. Our results on pulp weight was higher because it included moisture content of fresh pulp (sun dried) which ranges from 10 to 12% compared with oven dried values (Gruenwald and Galiza 2005).…”
Section: Fruit Variation Between and Within Provenancesmentioning
confidence: 99%
See 3 more Smart Citations